Automated Oxygen Delivery in Neonatal Intensive Care - Vrinda Nair; Vrinda Nair; Prakash Loganathan; Mithilesh Kumar Lal; Thomas Bachman (Frontiers Media S.A., 2022)
Oxygen is the most common drug used in the neonatal intensive care. It has a narrow therapeutic range in preterm infants. Too high (hyperoxemia) or low oxygen (hypoxemia) is associated with adverse neonatal outcomes. It is not only prudent to maintain oxygen saturations in the target range, but also to avoid extremes of oxygen saturations. In routine practice when done manually by the staff, it is challenging to maintain oxygen saturations within the target range. Automatic control of oxygen delivery is now feasible and has shown to improve the time spent with in the target range of oxygen saturations. In addition, it also helps to avoid extremes of oxygen saturation. However, there are no studies that evaluated the clinical outcomes with automatic control of oxygen delivery. In this narrative review article, we aim to present the current evidence on automatic oxygen control and the future directions.